The Effect of Digital Native Electronic Word-Of-Mouth (e-WOM) on Destination Awareness Tourism Village in West Java - Siti Nur Aini (Journal of Tourism Sustainability, 2022)
Tourism is a universal industry because every modern human considers that vacation is a need that must be fulfilled. In the digital era, there is a generation born and raised in technological developments called digital natives; this generation is considered a vital role holder in the tourism industry because, in the next few years, the digital native era will enter a productive age and do many things while on vacation. In their daily life, digital natives cannot be separated from social media and smartphones. This is a motivation to be able to develop a tourist village through the role of digital natives. This study has several objectives to achieve, namely to find out electronic word-of-mouth (e-WOM) on Instagram carried out by digital natives to determine destination awareness of tourist villages in West Java, as well as to examine the influence between e-WOM and destination awareness. This study uses quantitative methods through a descriptive verification approach with bivariate correlation analysis and simple linear regression. This study found the effect of electronic word-of-mouth on Instagram on destination awareness of West Java tourist villages, which was positive and significant, with a coefficient of determination of 22.3% and 77.7% influenced by other factors.